Privasi, Keamanan dan Niat Memakai Payment Fintech LinkAja pada UMKM Padang - Rika Desiyanti (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2022)
Abstract:         The study has purpose to analyze the effect of privacy and security on the intention to use LinkAja’s payment financial technology. Primary data needed and distribute questionnaire through google form. The sampling technique is simple random sampling with a total sample of one hundred and thirty-six respondents. This study using the Smart PLS program include: measurement model assessment (MMA), descrptive analysis, and structural model assessment (SMA). Results show, it can be conclude that privacy does have a positive effect on intentions to use payment financial technology, and also, security has a positive effect on intentions to use payment financial technology for SMEs’ Padang.Keywords:       Privacy, Security, Intention to Use Payment FintechAbstrak :        Studi ini mempunyai tujuan untuk menganalisis pengaruh privasi dan keamanan terhadap niat memakai payment financial technology LinkAja. Data primer dibutuhkan dalam penelitian ini. Data diperoleh dengan cara mendistribusikan kuesioner melalui google formulir. Teknik penarikan sampel adalah pengambilan sampel acak sederhana dengan jumlah total sampel seratus tiga puluh enam responden. Penelitian ini memakai program Smart PLS meliputi: measurement model assessment (MMA), analisis deskriptif dan structural model assessment (SMA). Dari hasil pengujian menunjukkan bahwa privasi berpengaruh positif terhadap niat memakai payment financial technology, dan keamanan juga berpengaruh positif terhadap niat memakai payment financial technology pada UMKM Padang.Kata Kunci:   Privasi, Keamanan, Niat Memakai Payment Fintech